2016
DOI: 10.1007/s00394-016-1306-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-glycemic-index diets in pregnancy on maternal and newborn outcomes in pregnant women: a meta-analysis of randomized controlled trials

Abstract: Low-GI diets may have beneficial effects on maternal outcomes for those at risk of developing high glucose levels, without causing adverse effects on newborn outcomes. However, results should be interpreted with caution because of the evidence of heterogeneity and limited number of studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 45 publications
2
41
0
3
Order By: Relevance
“…Controls retained on average 1.62 kg body weight from baseline to 6 months postpartum. In this study, women were advised to adhere to a low glycaemic index diet, in order to prevent repeat macrosomic births, which has been previously evaluated as a promising weight‐control strategy . However, precision estimates of the results of this follow‐up suggest high variability in the PPWR of participating women.…”
Section: Discussionmentioning
confidence: 99%
“…Controls retained on average 1.62 kg body weight from baseline to 6 months postpartum. In this study, women were advised to adhere to a low glycaemic index diet, in order to prevent repeat macrosomic births, which has been previously evaluated as a promising weight‐control strategy . However, precision estimates of the results of this follow‐up suggest high variability in the PPWR of participating women.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Zhang et al, [67] reviewed the effects of low-GI diets in all pregnant women, both those having healthy pregnancies, at risk for GDM, and those with GDM. In a total of 11 trials involving 1985 women, low-GI diets significantly reduced fasting and two-hour postprandial glucose level.…”
Section: Role Of Dietary Carbohydrates In Gdmmentioning
confidence: 99%
“…A recent meta-analysis of 11 randomized controlled trials involving 1985 women has shown that low-GI diets significantly reduce fasting and 2-h postprandial glucose levels, gestational weight gain, birth weight, and the proportion of babies born large for gestational age [61]. On the other hand, the results for body composition of the infant are less clear.…”
Section: Pregnancy Outcomementioning
confidence: 99%